2012
DOI: 10.1371/journal.pone.0040252
|View full text |Cite
|
Sign up to set email alerts
|

The Brain Network of Expectancy and Uncertainty Processing

Abstract: BackgroundThe Stimulus Preceding Negativity (SPN) is a non-motor slow cortical potential elicited by temporally predictable stimuli, customarily interpreted as a physiological index of expectancy. Its origin would be the brain activity responsible for generating the anticipatory mental representation of an expected upcoming event. The SPN manifests itself as a slow cortical potential with negative slope, growing in amplitude as the stimulus approximates. The uncertainty hypothesis we present here postulates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
4
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 55 publications
(65 reference statements)
6
50
4
4
Order By: Relevance
“…37,42,43 Decisions requiring cross-reference to the decision maker's value system, incorporation of long-term or contextual information and decisions made under uncertainty are known to burden the DLPFC. 20,38,[45][46][47] Finally, goal-directed DM specifically involves the anterior cingulate cortex during highly ambiguous situations in which the decision maker perceives several conflicting options and a high likelihood of error, 37,38 which also may explain the relative PFC redundancy among novices during primed intraoperative DM.…”
Section: Discussionmentioning
confidence: 99%
“…37,42,43 Decisions requiring cross-reference to the decision maker's value system, incorporation of long-term or contextual information and decisions made under uncertainty are known to burden the DLPFC. 20,38,[45][46][47] Finally, goal-directed DM specifically involves the anterior cingulate cortex during highly ambiguous situations in which the decision maker perceives several conflicting options and a high likelihood of error, 37,38 which also may explain the relative PFC redundancy among novices during primed intraoperative DM.…”
Section: Discussionmentioning
confidence: 99%
“…A cue showing a fistful of money indicated that a fast response would earn money (between $.05–$1.50); a fistful of burning money indicated that a fast response would avoid a loss; an empty palm indicated that no money could be gained or lost. Reward and loss amounts were varied on each trial in order to enhance participant engagement in the experimental task, as feedback uncertainty (lack of predictability) yields enhanced cortical correlates of engagement (Catena et al, 2012). A 1000 Hz auditory tone was presented concurrent with the preparatory cue to accentuate the announcement of the preparatory period (Wynn et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Hasta donde sabemos, no se ha estudiado la actividad dopaminér-gica tónica asociada a la incertidumbre en humanos. Sin embargo, tres estudios recientes (Catena et al, 2012;Fuentemilla et al, 2013;Morís, Luque y Rodríguez-Fornells, 2013) han encontrado en el mismo intervalo una señal cortical que también está directamente vinculada a la incertidumbre del resultado. Por ejemplo, Catena et al (2012) midieron la actividad electroencefalográfica que se produce en este intervalo.…”
Section: Fuentes De Recompensa En El Juego Vinculadas a La Actividad unclassified
“…Sin embargo, tres estudios recientes (Catena et al, 2012;Fuentemilla et al, 2013;Morís, Luque y Rodríguez-Fornells, 2013) han encontrado en el mismo intervalo una señal cortical que también está directamente vinculada a la incertidumbre del resultado. Por ejemplo, Catena et al (2012) midieron la actividad electroencefalográfica que se produce en este intervalo. Para ello utilizaron una tarea de aprendizaje predictivo, en la que se manipulaba la contingencia con la que un estí-mulo era capaz de predecir un resultado en una serie ensayos.…”
Section: Fuentes De Recompensa En El Juego Vinculadas a La Actividad unclassified
See 1 more Smart Citation